Acceptability and feasibility of an online psychosocial intervention for Dutch adolescents with a visible difference: A mixed-methods study. (June 2022) - van Dalen, M.; Pasmans, S.G.M.A.; Aendekerk, E.W.C.; Mathijssen, I.M.J.; Koudstaal, M.J.; Williamson, H.; Hillegers, M.H.J.; Utens, E.M.W.J.; Okkerse, J.M.E.
Abstract: Adolescents with a visible difference can experience difficult social situations, (e.g., people staring or making unwanted comments) and are at risk for mental health problems. Unfortunately, interventions for adolescents with a visible difference experiencing appearance-related distress are scarce and lack an evidence-base. This study tests the acceptability and feasibility of YP Face IT, an innovative online psychological intervention using social skills training and cognitive behavioural therapy, to Dutch adolescents. Adolescents aged 12–17 with a visible difference and access to an internet-enabled computer or tablet participated. They completed YP Face IT (eight sessions) and questionnaires were administered pre- and post-intervention. After completing YP Face IT, participants were interviewed to assess the acceptability and feasibility of YP Face IT and study procedures. Overall, 15 adolescents consented to participation, one person dropped out after one session. Most adolescents appreciated the intervention and all would recommend it to other adolescents experiencing appearance-related distress. Everyone reported learning experiences after following the sessions. Some struggled with motivation, but reminders by the website and research team were helpful. The Dutch YP Face IT intervention may be acceptable and the current study design is feasible to use. An RCT should be conducted to assess the effectiveness of the intervention. Highlights: YP Face IT is an online intervention for adolescents with a visible difference (81 characters). YP Face IT is acceptable and feasible to Dutch adolescents aged 12 – 17 (73 characters). YP Face IT helped adolescents manage difficult thoughts and social situations (80 characters). Around half of the adolescents preferred eHealth over face-to-face care (74 characters). A randomised controlled trial is required to test the effectiveness of YP Face IT (83 characters).